STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM UPAYA MENINGKATKAN MINAT MEMBACA AL-QUR’AN PADA SISWA SMP ISLAM AL-MAARIF SINGOSARI - Lailatul Sukarina Sagran; Abdul Jalil; Mohammad Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
In Indonesia, there are still mostly Muslim teenagers who are less interested in reading the Qur'an as well as in the school environment. The lack of interest in reading the Qur'an in these circles is caused by several factors. So that the phenomenon is the duty of PAI teachers to try to increase the interest in reading the Qur'an to students. So in this case the researcher wants to do research that is the case study at SMP Islam Al-Maarif located in Singosari sub-district, Malang Regency. The method used in this research is descriptive qualitative in the form of a case study approach. Where this research is more systematically directed at certain objects as a case. In the case study approach, data collection techniques can be sourced from the parties concerned or from various sources.. Based on data collection techniques carried out by researchers, is observation, interviews and documentation, the researchers conclude the results of the research obtained, namely: a) Less than the maximum teacher in guiding reading al-Qur'an so that there are still some students who are less able to read the Qur'an. b) The state of the class is less efficient so that makes students lazy when directed to read the Qur'an. c) The teacher is still not firm enough to make students accustomed to reading the Qur'an whether it is done at school or at home. d) the attitude of students who still have to read the Qur'an by being forced to read it every day.